Teak Leaf-Based Activated Carbon for Phosphate Removal (Jurnal Bahan Alam Terbarukan, 2019)
The use of detergent predictably causes large quantities of phosphate ion in water bodies. It is considered to trigger eutrophication, that creates a severe reduction in water quality. Adsorption using activated carbon is one of the effective methods for the removal of phosphate from wastewater. Recently, the use of microwave irradiation in activated carbon preparation is a promising alternative to replace conventional heating using a furnace. In this study, the use of microwave heating was compared to conventional heating. The result showed that pore of activated carbon was larger than that of the char and the activated carbon prepared using 30% of ZnCl2 had the adsorption performance higher than that of prepared using 20% of ZnCl2. The optimum adsorption occurred at pH 4 and the equilibrium was reached after 180 minutes. The Langmuir equilibrium model was more appropriate than the Freundlich equilibrium model. While the kinetics model analyzed using pseudo-first-order, pseudo-second-order, internal diffusion, and external diffusion indicated that the pseudo second order was most suitable for the adsorption of phosphate by teak leaf activated carbon.